Practice of Physical Activity by Elderly Frequenters of Basic Health Units - Daniel Vicentini Oliveira; Robson Lazzari de Brito; Mateus Dias Antunes; José Roberto Andrade do Nascimento Júnior; Caio Rosas Moreira; Dayane Capra de Oliveira; Maria do Carmo Correia de Lima; Sônia Maria Marques Gomes Bertolini; Cláudia Regina Cavaglieri (Brazilian Society of Geriatrics and Gerontology, 2024)
OBJECTIVES: This study aimed to identify the factors associated with the physical activity of elderly assisted at the basic health units (BHU) of the city of Matelândia, Paraná, Brazil. METHODS: This is a cross-sectional study, in which 343 elderly users of the BHU of this city were surveyed. A socio-demographic questionnaire, the International Physical Activity Questionnaire (IPAQ), and the questionnaire of barriers to physical activity practice were used. RESULTS: In relation to the level of physical activity, 88.9% of the elderlies were classified as active/very active. Higher level of physical activity was significantly associated with the amount of medication used (p = 0.024), reason to go to BHU (p = 0.037), and indication of physical activity by UBS (p = 0.040). Lack of energy (p = 0.048) was a more frequent and significant barrier for the active/very active elderly. CONCLUSION: There is a large number of active/very active elderly users of the BHU of Matelândia, Paraná, Brazil, and this was associated with lower age, lower medication use, going to BHU to withdraw medication/others and indication of physical activity by the BHU. For those who do not fit into these levels, lack of financial resources and insufficiently safe environment are the most common barriers to physical activity.